Impacts of watershed management and topographic positions on soil organic carbon and total nitrogen stocks in Northeast highlands of Ethiopia - Andualem Belay; Assefa Abegaz; Mohammed Assen (Trees, Forests and People)
Understanding soil organic carbon (SOC) and total nitrogen (TN) stock changes is crucial for designing effective strategies that sequester carbon and enhance soil fertility. This study examined the effects of slope aspect, watershed management practices, and slope position on SOC and TN stocks in the Upper Gelana watershed of Ethiopia. Sixty auger samples and sixty undisturbed core samples (0–30 cm) were collected. Data were subjected to a three-way general linear model. The results showed that watershed management practices and slope positions significantly influenced SOC and TN stock distributions (p < 0.05). Carbon-to-nitrogen ratios were affected considerably by slope aspect and slope position (p < 0.01). SOC stocks ranged from 20.65 Mg ha−1 in open grazing lands to 51.32 Mg ha−1 in natural forests, while TN stocks varied from 1.77 Mg ha−1 in traditional farming to 4.5 Mg ha−1 in controlled grazing systems. Both SOC and TN stock losses in open grazing and traditional farming reached 60 % and 59 %, respectively. Annual SOC stock gains in controlled grazing, agroforestry, and stabilized bund systems were 1.13, 0.82, and 0.51 Mg ha−1, respectively, with a 24-year restoration period. Natural forests had higher SOC and TN stocks in the east-facing aspect, while controlled grazing showed better results in the west-facing aspect. These findings emphasize the importance of expanding controlled grazing and agroforestry systems, alongside forest restoration, as an integrated watershed management approach for enhancing soil fertility and carbon sequestration. The results underscore the importance of considering topographic factors in land use planning to optimize nutrient dynamics.